Primary Cutaneous Diffuse Large B-Cell Lymphoma of the Upper Limb: Double Hit/Double Expressor with CNS Involvement: From Hospice to Remission - Brenda S. Castillo; Maria L. Rodriguez; Ju-Hsien John Chao; Behyar Zoghi (Case Reports in Hematology)
We report a patient with diffuse large B-cell lymphoma of skin, nongerminal center type double hit double expressor, with an initial presentation as a left forearm mass. The patient underwent chemotherapy after initial diagnosis. After chemotherapy regimen, she developed a second mass, followed by CNS involvement with neurological defects. At this time, a three line of chemotherapy was used with minimal effects. The patient was deemed terminal and was recommended hospice care. The patient decided to continue with skin and crainospinal radiotherapy and intrathecal chemotherapy; she achieved complete remission. After achieving complete remission, the patient underwent an autologous stem cell transplant with minimal transplant-related toxicity.